Moderation of Islam and Modern Western Culture: A Postcolonial Studies of Salah Asuhan Novel - Kamil, Sukron; Nisa, Mauidlotun (Buletin Al-Turas, 2024)
PurposeAmong the controversial issues in the 20th  century, even today, was the Islam's relationship with modern Western culture, whether it should be rejected, accepted, or critically accepted (adaptive adoption patterns). This article discussed this topic based on a study of Salah Asuhan by Abdoel Moeis as Idonesian Novel which was published in 1928. MethodThe study was conducted using a qualitative research method based on literature research enriched by a study of scientific literature. The theory used is the theory of postcolonialism and the construction of religious moderation of Islam. Results/findingsThis research found that the Salah Asuhan Novel was a construction of the author's moderate attitude towards Islam, its relationship with modern Western culture. In it, there was not only Moeis resistance to modern Western culture as a domination and a product of colonialism, but also adaptive adoption (hybridity), in which modern Western culture in general had to be handled by sorting/selecting. The pattern of Islamic moderation in the sense of a middle way was mostly adopted by Moeis,  although moderation was also adopted in the sense of emphasizing on upholding justice, considering the public benefit, especially eliminating inhuman difficulties as a point of view.  ConclusionIn cultural issues, Moeis in the novel tended to have to not fully accept modern Western culture. For example on science and technology, humanism, including feminism, the importance of legal evidence such as marriage with a legal marriage certificate, and educational patterns that emphasize religion, but also modern science.